SAK ETAP-BASED AGRICULTURAL (SUGARCANE) ACCOUNTING A DESCRIPTIVE ANALYSIS STUDY - Emir Faishal Baihaqi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims at identifying costs paid by sugarcane farmers in running their business process, identifying their assets, and helping them by providing samples of financial report appropriate to their business. The report is based on SAK ETAP since their business is not the major one and the report is not for publication. This qualitative descriptive study was held from May to October 2015 around Tjandi Baru sugar factory in Sidoarjo and around Krebet sugar factory, in which the farmers of the surrounding factories are the object. The data are collected through in-depth interviews, observations, and documentation.Keywords: qualitative descriptive, SAK ETAP, sugarcane farmers, agricultural accounting, cost accounting